Использование беспилотных летательных аппаратов для безопасности функционирования линий электропередачи - Гриб, Олег Герасимович; Зуев, Андрей Александрович; Шевченко, Сергей Юрьевич; Швец, Сергей Викторович; Иерусалимова, Татьяна Сергеевна; Бортников, Александр Викторович (НТУ "ХПИ", 2017)
Статья посвящена описанию алгоритма комплексного автоматизированного мониторинга ЛЭП энергетической системы, направленного на обеспечение безопасности функционирования ее оборудования и персонала. Как показывает анализ причин отказов ЛЭП, они в основном происходят на ЛЭП 110 кВ - 86 %, 11 % - на ЛЭП 220 кВ и 3 % ЛЭП 330-750 кВ. Такое распределение числа отказов пропорционально длине соответствующих ЛЭП. Наибольшее число аварийных отключений ЛЭП вызвано повреждением проводов и грозозащитных тросов - 56 %. Другими причинами, вызывающими отключения ЛЭП, являются такие повреждения как пробой изоляторов - 19 %, повреждения опор - 15 % и других элементов ЛЭП - 10 %.

The article is devoted to the description of the algorithm integrated automated monitoring of power lines power system, aimed at ensuring the safe operation of its equipment and personnel. As shows the analysis of the causes of failures of power lines, they mainly occur on the transmission line 110 kV – 86 %, 11 % - for transmission lines 220 kV and 3% transmission lines 330-750 kV. Such a distribution of the number of failures in proportion to the length of corresponding transmission lines. The greatest number of outages of transmission line caused by a damaged wire and ground wire is 56 %. Other reasons causing outage of the transmission line are such damage as a breakdown of insulators – 19 %, damage of supports to 15% and other elements of the LEP – 10 %. According to statistics, a sharp increase in outages of transmission lines occur in the spring and summer because of the ceiling insulation by green spaces. A fair number of outages of transmission lines due to vandalism, such as destruction of garlands insulators, theft of wires and elements of electric poles, lashed out at wire transmission lines etc.
The use of unmanned aerial vehicles for the safe functioning of transmission lines
Keywords: беспилотный летательный аппарат; мониторинг; электроэнергия; тепловизор; ЛЭП; БПЛА; электрическое поле; магнитное поле; monitoring; power line; electricity; thermal imager